Peran Koperasi Syariah ‘BAROKAH” SMK Batik 2 Surakarta dalam Mensejahterakan Anggota Melalui Pemberian Pembiayaan - Endwie Hidayat; Iin Emy Prastiwi; Sumadi (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the role of the “Barokah” Sharia Cooperative at SMK Batik 2 Surakarta in improving the welfare of its members through financing, as well as to examine the impact of such financing on members’ economic conditions. This research employs a qualitative approach, with data collected through interviews and observations. The results indicate that the “Barokah” Sharia Cooperative operates based on sharia principles derived from the Qur’an and Hadith, ensuring that all activities comply with Islamic law and provide benefits to its members. Furthermore, the management of the cooperative by individuals with a strong understanding of Islamic economics plays a crucial role in enhancing members’ awareness of the benefits and advantages of sharia-based transactions. The financing provided has proven to help meet members’ financial needs and contribute to improving their welfare. Therefore, the “Barokah” Sharia Cooperative serves as an alternative financial institution aligned with sharia principles and supports the sustainable economic development of its members.